Pulsed Generation of Quantum Coherences and Non-classicality in Light-Matter Systems - Gómez-Ruiz, Fernando J.; Acevedo, Oscar L.; Rodríguez, Ferney J.; Quiroga, Luis; Johnson, Neil F. (Frontiers in Physics, 2018)
We show that a pulsed stimulus can be used to generate many-body quantum coherences in light-matter systems of general size. Specifically, we calculate the exact real-time evolution of a driven, generic out-of-equilibrium system comprising an arbitrary number N qubits coupled to a global boson field. A novel form of dynamically-driven quantum coherence emerges for general N and without having to access the empirically challenging strong-coupling regime. Its properties depend on the speed of the changes in the stimulus. Non-classicalities arise within each subsystem that have eluded previous analyses. Our findings show robustness to losses and noise, and have potential functional implications at the systems level for a variety of nanosystems, including collections of N atoms, molecules, spins, or superconducting qubits in cavities – and possibly even vibration-enhanced light harvesting processes in macromolecules.